Peranan Guru Pendidikan Agama Islam Dalam Meningkatkan Kedisiplinan Ibadah Shalat Siswa SMP Negeri 22 Makassar - Nur Fadillah; Mawardi Pewangi; Sitti Satriani (Yayasan Al-Afif, 2025)
This research aims to (1) describe the role of Islamic Education teachers in improving students’ discipline in performing prayers at SMP Negeri 22 Makassar, (2) describe the forms of prayer discipline among students at SMP Negeri 22 Makassar, and (3) explain the obstacles faced by Islamic Education teachers in fostering students’ prayer discipline at SMP Negeri 22 Makassar. This study employs a qualitative descriptive method and was conducted at SMP Negeri 22 Makassar, located at Jl. Ir. H. Juanda No. 7, Ujung Pandang Baru, Tallo District, Makassar City, South Sulawesi Province. The research subjects include the school principal, Islamic Education teachers, and students. The research instruments used were observation, interview guidelines, and documentation guidelines. Data analysis techniques consisted of data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) The role of Islamic Education teachers in improving students’ prayer discipline involves several aspects: teachers act as guides by inviting and instructing students to participate in religious activities such as daily prayers and recitations of Asmaul Husna; teachers act as role models by demonstrating exemplary attitudes, behaviors, and guidance; and teachers implement habituation practices by organizing scheduled religious activities at school. (2) The forms of students’ prayer discipline at SMP Negeri 22 Makassar are fostered through various approaches, such as performing congregational prayers together and providing direct guidance, which ultimately helps students become more disciplined and develop awareness of performing prayers. This awareness serves as an important foundation for students to build the habit of fulfilling their religious obligations in daily life. (3) The obstacles faced by Islamic Education teachers in promoting students’ prayer discipline include students’ lack of awareness, diverse backgrounds, and limited facilities.